Effect of climate variability on the incidence of dengue in Palmira, Colombia (2010-2015) - Montoya-Rojas, Maira; Noguera-David, Diana; Fuertes-Bucheli, Jose; Pacheco-López, Robinson (Universidad y Salud, 2025)
Introduction: Sociocultural and economic conditions as well as climate variability can affect the incidence of dengue. Objective: To determine the impact of climate variability on the frequency of dengue cases in Palmira, Colombia, between 2010 and 2015. Materials and methods: Ecological and exploratory study, which related temperature, precipitation, and reported and confirmed cases of dengue. The frequency of dengue as well as its annual and monthly averages and medians were registered. The Pearson’s correlation coefficient was used to analyze cases and climate variables. Results: 2,832 cases of dengue were analyzed during the study period, with an annual average of 472. The association between the analyzed climate variables and the incidence of dengue was confirmed in 65 % of the cases. In 2010, the highest incidence of dengue and the highest average rainfall level were both reported. Also, the incidence of dengue increased coincidentally after the end of La Niña Phenomenon (2011). Conclusion: Between 2010 and 2015, a correlation between the incidence of dengue and climate variables (temperature and precipitation) was found in Palmira. However, future studies should analyze sociodemographic, cultural, behavioral, and geographic variables to better understand the dynamics of dengue.